PERSISTENSI DAN PEMATAHAN DORMANSI BENIH CABAI RAWIT LOKAL MENGGUNAKAN TEKNIK BIO-INVIGORASI BENIH - Saputra, Jefi; Amir, Riska Audina; Mumin, Nur; Sutariati, Gusti Ayu Kade (Jurnal Agrotek Tropika, 2020)
Persistence and Breaking of Local Chilli Seed Dormancy Using Seed Bio-Invigoration Techniques. This study aims to evaluate the persistence of local chilli seed dormancy while evaluating seed bio-invigoration techniques that effectively break the dormancy of local chilli. The study consisted of two series of experiments, namely: the persistence test of local chilli. seed dormancy (Series 1) was observed descriptively using a germination indicator for several weeks to reach a germination percentage ≥ 80%. Testing of seed dormancy breakage by seed bio-invigoration technique (Series 2) using a randomized complete design with 3 replications and 7 treatments namely: no treatment (A0), matriconditioning of husk charcoal powder (SAS) + Bacillus sp. CKD061 (A1), matriconditioning SAS + Pseudomonas sp. TBT214 (A2), red brick powder matriconditioning (SBM) + Bacillus sp. CKD061 (A3), matriconditioning SBM + Pseudomonas sp. TBT214 (A4), matriconditioning SAS + Bacillus sp. CKD061 + Pseudomonas sp. TBT214 (A5), and matriconditioning SBM + Bacillus sp. CKD061 + Pseudomonas sp. TBT214 (A6). The results showed that the persistence of local chilli seed dormant cultivars Konsel 1 and Konsel 2 cultivars were 6 weeks. While the dormancy break test on the Konsel 1 cultivar was 2 weeks at A1 treatment with breaking dormancy of 90.00%. While in Konsel 2 cultivar which is 4 weeks in the A6 treatment with breaking dormancy 86.67% which is significantly different from the control. This study shows that A1 treatment can break dormancy of chilli seeds in Konsel 1 cultivar and A6 treatment in Konsel 2 cultivar.